2017
DOI: 10.3928/01477447-20170308-02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Platelet-Rich Fibrin on Long Bone Healing: An Experimental Rat Model

Abstract: Pseudoarthrosis, or nonunion, of the long bones is a challenging medical condition for orthopedic surgeons to treat. Therefore, healing enhancer materials are commonly used. The authors investigated whether platelet-rich fibrin accelerates long bone healing by comparing radiological and histological findings in a rat model of open femoral fracture. Platelet-rich fibrin is a current biomaterial that contains many growth factors and platelets. There are no studies in the literature investigating the effects of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
1
21
0
3
Order By: Relevance
“…This is due to the presence of PRF, and when activation of these platelets will secrete more than 300 bioactive substances from its granules, these growth factors and cytokines responsible for attracting the phagocytes, stem cells and osteoblast. Therefore its responsible for removing of damage and necrotic tissue rather than stimulates and contributes regeneration of tissues and accelerate healing of damaged tissues, and this is agree with Davis et al, Everts et al, Dülgeroglu & Metineren (18,22,26), whom confirmed that, the platelets its an active biomaterial in the healing of fractures and it increases the amount of formation of bone tissue by reducing the inflammatory period to promote and compensation of fracture healing stage.…”
Section: Discussionsupporting
confidence: 75%
“…This is due to the presence of PRF, and when activation of these platelets will secrete more than 300 bioactive substances from its granules, these growth factors and cytokines responsible for attracting the phagocytes, stem cells and osteoblast. Therefore its responsible for removing of damage and necrotic tissue rather than stimulates and contributes regeneration of tissues and accelerate healing of damaged tissues, and this is agree with Davis et al, Everts et al, Dülgeroglu & Metineren (18,22,26), whom confirmed that, the platelets its an active biomaterial in the healing of fractures and it increases the amount of formation of bone tissue by reducing the inflammatory period to promote and compensation of fracture healing stage.…”
Section: Discussionsupporting
confidence: 75%
“…In recent years, particular attention has been given to the potential for interaction between platelet concentrates and bone healing. In an experimental rat model of femoral fracture, Dülgeroglu and Metineren [ 12 ] observed increased bone formation after 28 days of healing when PRF clots were applied to bone. Similarly, Nagata et al [ 13 ] observed significantly increased bone formation in surgically created bone defects in rat calvaria treated with a combination of autogenous bone graft and platelet-rich plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets take part in creating the fibrin thrombus. This acts as a scaffold for cellular engraftment as platelets secrete inflammatory cytokines (IL-1, IL-6, TNF-α) and growth factors (PDGF, TGF-beta) to recruit other immune cells (neutrophils and monocytes) and mesenchymal progenitor cells respectively [ 27 29 ].…”
Section: Bone Fracture Healingmentioning
confidence: 99%